Flow Cytometry and Solid Organ Transplantation: A Perfect Match. (November 2014) - Maguire, Orla; Tario, Joseph D.; Shanahan, Thomas C.; Wallace, Paul K.; Minderman, Hans
<x xml:space="preserve">Abstract</x> In the field of transplantation, flow cytometry serves a well-established role in pre-transplant crossmatching and monitoring immune reconstitution following hematopoietic stem cell transplantation. The capabilities of flow cytometers have continuously expanded and this combined with more detailed knowledge of the constituents of the immune system, their function and interaction and newly developed reagents to study these parameters have led to additional utility of flow cytometry-based analyses, particularly in the post-transplant setting. This review discusses the impact of flow cytometry on managing alloantigen reactions, monitoring opportunistic infections and graft rejection and gauging immunosuppression in the context of solid organ transplantation.